"A Playing Field Where Patriarchy Plays": Addressing Sexism in South African and Nigerian Newsrooms. (21st April 2022) - Blumell, Lindsey E.; Mulupi, Dinfin
ABSTRACT: This study uses in-depth interviews from journalists to examine gendered norms in newsrooms in South Africa and Nigeria. It incorporates the organizational and social system levels of gatekeeping to identify problematic work environments and influential cultural attitudes towards gender. Participants from both countries identified sexual abuse, sexual harassment, unfair job allocations, limited access to power, unfair pay, and overall unsafe work environments as significant problems. Nigerian participants stressed the influence of culture and religion, whereas South African participants also discussed race. Participants described varying degrees of organizational interventions and restitutions, but overall agreed organizations could do more. Cultural rape myths such as excusing the seriousness of sexual abuse, slut shaming, and victim blaming were more common with Nigerian participants. Solutions from participants mainly focused on promoting more women to managerial positions and newsroom training. However, many expressed the difficulties of eradicating sexism in journalism because of its pervasiveness in society.